Exploring the Prognostic Role of Trop-2, CD47, and CD163 Expression Levels on Survival Outcomes in Patients with Triple-Negative Breast Cancer - Ramazan Oguz Yüceer; Sedanur Aydın; Iclal Gelir; Tulay Koc; Ersin Tuncer; Mahmut Ucar (Diagnostics)
Background: This study evaluated the prognostic impact of Trop-2, CD47, and CD163 expression on clinical outcomes in triple-negative breast cancer (TNBC) and investigated their interactions with tumor progression. Methods: A retrospective cohort of 92 patients with TNBC was analyzed. The expression scores for Trop-2, CD47, and CD163 were categorized as negative/low (0–3 points) or high (4–6 points). The primary endpoint was overall survival (OS). Results: The median age of the cohort was 50 years old. High Trop-2 expression was observed in 55.4% of the patients and was significantly associated with advanced disease stage (p < 0.001). High CD47 expression (44.6%) was correlated with advanced stage (p = 0.044), whereas high CD163 expression (45.7%) was associated with advanced stage (p = 0.021), absence of comorbidities (p = 0.022), and lower pT stage (p = 0.023). Moderate positive correlations were found between Trop-2 and CD47 (p = 0.022), Trop-2 and CD163 (p = 0.037), and CD47 and CD163 (p < 0.001), respectively. Kaplan–Meier survival analysis revealed that patients with low Trop-2 expression exhibited significantly prolonged OS (p = 0.021) and progression-free survival (PFS) (p = 0.026) compared to those with high Trop-2 expression. Univariate and multivariate analyses revealed significant associations between OS and PFS for Trop-2, lymphovascular invasion, and BRCA status. Conclusions: Trop-2 expression is a significant prognostic factor for TNBC and is correlated with worse outcomes. Although CD47 and CD163 showed trends for poorer prognosis, their significance was not confirmed. These findings offer promising prospects for future studies on combined antibody–drug conjugates (ADCs), as they may present opportunities to address multiple resistance mechanisms in the management of TNBC and enhance clinical outcomes.